Promoting correct positioning and attachment in breastfeeding infants born by section cesarean in the La Fe Hospital in Spain: a best-practice implementation project. Issue 3 (8th September 2020) - Saus-Ortega, Carlos
ABSTRACT: Aim: The aim of this project was to assess compliance with evidence-based criteria that set out effective techniques for ensuring correct positioning and attachment in breastfeeding infants delivered by cesarean section in the La Fe University and Polytechnical Hospital of Valencia, Spain. Methods: The current clinical pre/post audit was conducted in a convenience sample with no control group. First, five audit criteria from the JBI framework and Practical Application of Clinical Evidence System program were selected to assess correct positioning and attachment during breastfeeding. We then conducted a baseline audit to determine the degree of compliance with these criteria. Second, we used the Getting Research into Practice guidelines to help us identify obstacles to fulfillment of each criterion and to design and implement various strategies to improve compliance. Third, a follow-up audit was performed and the degree of compliance of each criterion was determined again. Finally, the barriers to implementation of the strategies were identified. Results: Eighty-seven mothers and 20 midwives participated in the baseline audit and 93 mothers and 17 midwives took part in the follow-up audit. After implementation, the rates of compliance with the three maternal criteria (2, 3, and 4) significantly improved. These were guidance to women, breastfeeding support, and encouragement from families, which increased by 42, 49, and 51%, respectively. Furthermore, criterion 4 (professional training programs) reached 100% compliance. However, criterion 1 (skin-to-skin contact) only increased by 2%. Eight barriers were described, including a lack of knowledge of the skin-to-skin procedure, a hands-on approach to breastfeeding support, a lack of time or high workload, and differences in the breastfeeding support provided by different professionals. Implementing strategies such as assessment with the LATCH scale, continuing the support of breastfeeding mothers through working shift changes, and promoting the skin-to-skin procedure, proved to be effective. Conclusion: The current audit project significantly improved all our evidence-based criteria used to promote correct positioning and attachment during breastfeeding in women who had given birth by cesarean section. We accomplished this goal by developing several strategies which were accepted and implemented by all the midwives involved. Early, adequate, and ongoing support for breastfeeding women during postpartum hospitalization was key to the success of this project. It will be important to improve the skin-to-skin parameter in the surgical block in the near future to further consolidate and improve these results.